Application of MATLAB software in the learning of the linear kinematics of a particle in university engineering students (Revista Innova Educación, 2019)
The objective of this research was to determine the effectiveness of MATLAB software in the application of differential calculus in linear kinematics of a particle in engineering students of the National University of Juliaca, in order to optimize the academic performance of these students. The research design that has been assumed was the quasi-experimental. For the collection of information, the kinematic knowledge test of a particle has been used. The sample of the investigation has been conformed of the students of the second semester of Textile and Apparel Engineering. The results indicate that of 100% of the students in the experimental group, 9% is in the very good category, while in the control group 0% remains in the very good category.
Keywords: Differential calculus; learning; MATLAB; kinematics; physics